MUZÍKA HÁM ART - PEDAGOGIKA - Erejepov, A.A. (SCIENCE and SOCIETY, 2022)
One of the directions in the field of natural science education today is art pedagogy. Art pedagogy is a branch of the discipline of pedagogy, which is associated with pedagogy and art. "Art" - (from English) - art, "pedagogy" - the subject of education and upbringing of the individual. These two words refer to the two most important things in a person's life: learning through art or learning as art. The term "art pedagogy" appeared in the middle of the last century.